Design formulae for Long-Term responses of continuous Steel-Recycled aggregate concrete composite slabs. (November 2022) - Zhang, Huan; Zhang, Hai-Yan; Geng, Yue; Fang, Peng-Qi; Wang, Yu-Yin
Abstract: The steel-recycled aggregate concrete (RAC) composite slab is a low-carbon structural member with higher constructional efficiency. However, no design method has been established for the serviceability limit state evaluation of such members accounting for long-term effects. The non-uniform shrinkage peculiar to composite slabs significantly deteriorates the long-term responses of slabs, which would be more significant when using RAC. Previous studies only focused on the long-term responses of simply-supported composite slabs using NAC. The investigated responses include member deflection and stress in steel decking. No research attention has been paid to the continuous composite slabs, in which non-uniform shrinkage further induces possible yielding of the negative reinforcement and the limit exceeding of concrete crack width in the negative moment zone. Furthermore, the recycled aggregate influence has not been accounted for in the long-term design of the composite RAC slabs. In this context, this study aims to establish simplified explicit design formulae for the long-term responses of continuous RAC composite slabs accounting for the non-uniform shrinkage effects and the recycled aggregate influence. The target long-term responses include deflection, steel decking stress, negative reinforcement stress, and the concrete crack width in the negative moment zone. The simplified explicit formulae were derived from cross-sectional analysis results with some variables reasonably simplified into constant values based on collected data from real applications. The validation results have shown that the proposed formulae are capable of predicting the long-term responses of continuous RAC composite slabs, with the prediction accuracy similar to the code formulae for reinforced concrete slabs.